elime os parenteses colchetes e chaves e reduza os termos semelhantes 2y-[-xy+(-2x+5y)-(-4xy+x)]
Soluções para a tarefa
Respondido por
1
2y-[-xy+(-2x+5y)-(-4xy+x)]
=
=2y-[-xy-2x+5y+4xy-x]
=2y-[-xy+4xy-2x-x+5y]
=2y-[+3xy-3x+5y]
=2y-3xy+3x-5y
=2y-5y-3xy+3x
=-3y-3xy+3x
ou
=-3xy+3x-3y
=2y-[-xy-2x+5y+4xy-x]
=2y-[-xy+4xy-2x-x+5y]
=2y-[+3xy-3x+5y]
=2y-3xy+3x-5y
=2y-5y-3xy+3x
=-3y-3xy+3x
ou
=-3xy+3x-3y
Perguntas interessantes
Português,
1 ano atrás
Português,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Ed. Física,
1 ano atrás
Biologia,
1 ano atrás
História,
1 ano atrás
História,
1 ano atrás